A Hybrid Security Mechanism for Intra-WBAN and Inter-WBAN Communications. (21st August 2013) - Irum, Sarah; Ali, Aftab; Khan, Farrukh Aslam; Abbas, Haider
Abstract : The emerging wireless body area networks (WBANs) have a great potential for the growth and development of future ubiquitous healthcare systems. However, due to the use of unreliable wireless media, WBANs are exposed to a variety of attacks. The prevention of these attacks depends upon the cryptographic techniques. The strength of cryptography is based on the keys used for encryption and decryption in the communication process. Security is still an alarming challenge for WBANs and needs attention of the research community. The proposed work introduces a hybrid key management scheme for both intra-WBAN and inter-WBAN communications. The proposed technique is based on preloaded keys as well as keys automatically generated from biometrics of the human body. The biometric-based calculations are of linear time complexity to cater the strict resource constraints and security requirements of WBANs. The proposed security mechanism provides an efficient solution for the security of both intra-WBAN and inter-WBAN communications. The results of the proposed technique are compared with an existing key management technique known as BARI+. The results show significant improvement over the results produced by BARI+ in terms of storage, communication, energy overhead, and security.